2003
DOI: 10.1103/physrevc.68.058201
|View full text |Cite
|
Sign up to set email alerts
|

Exclusive electromagnetic production of strangeness on the nucleon: Regge analysis of recent data

Abstract: In view of the numerous experimental results recently released, we provide in this letter an update on the performance of our simple Regge model for strangeness electroproduction on the nucleon. Without refitting any parameters, a decent description of all measured observables and channels is achieved. We also give predictions for spin transfer observables, recently measured at Jefferson Lab which have high sensitivity to discriminate between different theoretical approaches.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…[24] it is demonstrated that, even when using the asymptotic form of the propagators, the order of magnitude of the forward-angle pion and kaon photoproduction observables in the resonance region is remarkably well reproduced in a pure t-channel Regge model. A similar observation holds for kaon electroproduction [34]. These results imply that at forward angles, the global features of the p(γ, K + )Λ reaction in the resonance region can be reasonably well reproduced in terms of background diagrams, with resonance effects constituting relatively minor corrections.…”
Section: B Inclusion Of Resonance Dynamicssupporting
confidence: 72%
“…[24] it is demonstrated that, even when using the asymptotic form of the propagators, the order of magnitude of the forward-angle pion and kaon photoproduction observables in the resonance region is remarkably well reproduced in a pure t-channel Regge model. A similar observation holds for kaon electroproduction [34]. These results imply that at forward angles, the global features of the p(γ, K + )Λ reaction in the resonance region can be reasonably well reproduced in terms of background diagrams, with resonance effects constituting relatively minor corrections.…”
Section: B Inclusion Of Resonance Dynamicssupporting
confidence: 72%
“…Following the convention of the VGL [4][5][6][7] and the Reggeplus-resonance (RPR) [9][10][11][12] models, the "mass scale" s 0 is fixed to s 0 = 1 GeV 2 . In Ref.…”
Section: Transition Currentsmentioning
confidence: 99%
“…In this regard it is worth noting that the measured p(γ * ,K + )Λ unseparated cross section σ U at high energies can be reproduced by the Vanderhaeghen-Guidal-Laget (VGL) model [4][5][6][7] after introducing an effective kaon EM form factor. The kaon EM cutoff energy employed in the VGL model is significantly increased compared to the value extracted from elastic eK scattering.…”
Section: Introductionmentioning
confidence: 99%
“…Data involving known baryon resonances of spin J ≤ 3/2 and later J ≤ 5/2 were fitted and γN, πN, ππN, ηN and KΛ partial widths were extracted [16,17,18,19,20]. The data have also been interpreted by Regge-model calculations [21] using only K and K * exchanges and no s-channel resonances. Only the gross features of the data were reproduced.…”
Section: Introductionmentioning
confidence: 99%